Teacher Strategies for Fostering Students' Learning Interest in Islamic Religious Education: A Qualitative Study in an Indonesian Junior High School - Feriska Nurhayat; Edi Saputra (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study investigates the factors contributing to students' low interest in learning Islamic Religious Education, examines the pedagogical strategies employed by teachers to foster learning interest, and explores the perceived effectiveness of these strategies in an Indonesian junior high school context. A qualitative descriptive approach was employed at SMP Negeri 2 Lubuk Basung, Indonesia. Data were collected through in-depth interviews with one Islamic Religious Education teacher, the vice principal for curriculum affairs, and seven seventh-grade students, complemented by classroom observations and document analysis. The data were analyzed using data reduction, data display, and conclusion drawing with source triangulation to enhance trustworthiness. The findings reveal that students' low learning interest results from the interaction between internal factors, including limited intrinsic motivation and perceptions of IRE as theoretical and memorization-oriented, and external factors, such as teacher-centred instruction, limited instructional media, inadequate learning time, unconducive classroom conditions, and insufficient family support. Teachers addressed these challenges through student-centred strategies, including Project-Based Learning, Problem-Based Learning, collaborative discussions, multimedia integration, classroom management, and continuous motivational support, which increased classroom participation from approximately 30% to 45–60%. However, improvements remained context-dependent and students' independent learning habits were still limited. This study extends the literature by demonstrating that students' learning interest develops through the interaction between pedagogical practices, supportive classroom environments, and students' self-directed use of digital religious learning resources beyond formal instruction. The study provides a contextual pedagogical framework for fostering learning interest in Islamic Religious Education and offers practical implications for teachers and schools seeking to develop more engaging, student-centred, and digitally integrated religious learning environments.